Rural poverty reduction through business partnerships?: examples of experience from the forestry sector - Vermeulen, Sonja J.; Nawir, A.A.; Mayers, J. (Springer, 2008)
At the Earth Summit in Johannesburg in 2002, partnerships were touted as one of the key routes to sustainable development. But can partnerships really deliver improvements to rural livelihoods? This paper reviews one set of claimed partnerships, those between forestry companies and local individuals or communities, to assess the benefits, and the costs, to local livelihoods. Most arrangements between forestry companies and local communities are not equitable enough to be called partnerships, so the term ‘‘deal’’ is preferred. Positive local impacts of company–community deals include sharing of risks, better returns to land than otherwise possible, opportunities for income diversification, access to paid employment, development of new skills, upgrading of local infrastructure and environmental improvement. However, company–community deals have not yet proved sufficient to lift people out of poverty. They remain supplementary rather than central to income generation. Furthermore, while some deals have resulted in greater cohesion and organisation among community groups, there is as yet little evidence of substantial increases in community bargaining power. Ways forward to increase returns to communities (and to their counterpart companies) centre on moving towards more equal partnerships, by raising community bargaining power, fostering the roles of brokers and other third parties, and developing equitable, efficient and accountable governance frameworks.